How Attending Physician Preceptors Negotiate Their Complex Work Environment: A Collective Ethnography. (December 2017) - Lemaire, Jane B.; Wallace, Jean E.; Sargious, Peter M.; Bacchus, Maria; Zarnke, Kelly; Ward, David R.; Ghali, William A.
Abstract : Purpose: To generate an empiric, detailed, and updated view of the attending physician preceptor role and its interface with the complex work environment. Method: In 2013, the authors conducted a modified collective ethnography with observations of internal medicine medical teaching unit preceptors from two university hospitals in Canada. Eleven observers conducted 32 observations (99.5 hours) of 26 preceptors (30 observations [93.5 hours] of 24 preceptors were included in the analysis). An inductive thematic approach was used to analyze the data with further axial coding to identify connections between themes. Four individuals coded the main data set; differences were addressed through discussion to achieve consensus. Results: Three elements or major themes of the preceptor role were identified: (1) competence or the execution of traditional physician competencies, (2) context or the extended medical teaching unit environment, and (3) conduct or the manner of acting or behaviors and attitudes in the role. Multiple connections between the elements emerged. The preceptor role appeared to depend on the execution of professional skills (competence) but also was vulnerable to contextual factors (context) independent of these skills, many of which were unpredictable. This vulnerability appeared to be tempered by preceptors' use of adaptive behaviors and attitudes (conduct), such as creativity, interpersonal skills, and wellness behaviors. Conclusions: Preceptors not only possess traditional competencies but also enlist additional behaviors and attitudes to deal with context-driven tensions and to negotiate their complex work environment. These skills could be incorporated into role training, orientation, and mentorship.